2003
DOI: 10.1029/2002gl016471
|View full text |Cite
|
Sign up to set email alerts
|

Controls of dust emissions by vegetation and topographic depressions: An evaluation using dust storm frequency data

Abstract: [1] The degree to which dust emissions are controlled by vegetation cover and geomorphic setting (specifically closed topographic depressions) was investigated using dust storm frequency (DSF) data based on visibility measurements from >2400 meteorological stations worldwide. Comparisons with distributions of vegetation types suggest that DSF is highest in desert/bare ground (median: 60-80 d/yr) and shrubland (median: 20-30 d/yr) regions, and comparatively low in grassland regions (median: 2 -4 d/yr). Average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
108
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(114 citation statements)
references
References 11 publications
(25 reference statements)
4
108
1
1
Order By: Relevance
“…However, interpreting the dust storm frequency dataset used in Engelstaedter et al (2003) as blowing dust or sand makes this dataset consistent with the results of this and other previous studies which analyzed data at particular stations (e.g. N'Tchayi Mbourou et al, 1997).…”
Section: Visibility Trends and Correlations In Dust Regionssupporting
confidence: 80%
See 2 more Smart Citations
“…However, interpreting the dust storm frequency dataset used in Engelstaedter et al (2003) as blowing dust or sand makes this dataset consistent with the results of this and other previous studies which analyzed data at particular stations (e.g. N'Tchayi Mbourou et al, 1997).…”
Section: Visibility Trends and Correlations In Dust Regionssupporting
confidence: 80%
“…4 and Table 4), we obtain no statistically significant correlations with either topographic lows or human land use variables. However, if we use the dust storm frequency dataset described in Engelstaedter et al (2003) i. j. of I. Tegen and S. Engelstaedter), we obtain similar results to those obtained in that study (Fig. 4 and Table 4) -the dustiness in this dataset is correlated with natural dry lake beds, and not with land use proxies.…”
Section: Visibility Trends and Correlations In Dust Regionssupporting
confidence: 74%
See 1 more Smart Citation
“…The long-term dust variability studies based on meteorological observations present up to 90 year old records from North America, Africa, Asia and Australia (N'TchayiMbourou et al, 1997;Qian et al, 2002;Natsagdorj et al, 2003;Ekström et al, 2004;Jamalizadeh et al, 2008;Steenburgh et al, 2012). Engelstaedter et al (2003) reported high dust activity at many weather stations located in high-latitude regions. Cold climate regions are represented by long-term dust frequency in Northeast (NE) Iceland (Dagsson-Waldhauserova et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed and longterm studies on wind erosion variability can potentially explain the climatological and environmental changes in the past. Periodical dust occurrences can affect ecosystem fertility and spatial and temporal distribution of animal and vegetation species similarly to climate variations (Fields et al, 2010). Oceanic ecosystems receive high amounts of nutrient rich dust spread over large areas where deserts occur near the sea .…”
Section: Introductionmentioning
confidence: 99%